A Remote Controlled Car Using Wireless Technology - Joni Welman Simatupang; Michael Yosua (Journal of Electrical And Electronics Engineering, 2016)
Automation or automatic control is the use of various control system for operating any equipment or device such as a remote controlled (toy) car, switching on telephone networks, and other useful applications with minimal or reduced human interventions. This paper proposes a design and implementation of a remote controlled car by wi-fi technology via computer or mobile devices. In completing this research work, wireless software and hardware technologies have been used, such as wireless module of ESP8266 for transceiver (transmitter and receiver), Arduino Uno as microcontroller, an H-bridge L293D IC for motor controller, and two electric DC motors are used to move the automobile. Two objectives of this project are to expand the limitation range of a normal radio  frequency car using wi-fi technology and also to create a ubiquitous technology for automobile that operates in daily life with a control system. The test result shows that the controlled car can move in any direction. However, the performance depends on the device signal strength where the maximum testing range is only about 20 meters’ distance from the user’s location.Keywords: automation, wi-fi technology, remote controlled car, Arduino, signal strength.